La modernidad insufrible : Roberto Bolaño en los límites de la literatura latinoamericana contemporánea - Zavala, Oswaldo, 1975- (Book collections on Project MUSE., 2015)
Has Chilean author Roberto Bolano (1953-2003) written the final word on Latin America's insufferable modernity? This investigation asserts that Bolano's novels, short stories, poetry and essays examine to a point of exhaustion the most important aspects of Latin America's modern literary tradition. Bolano's critique of modernity as a violent historical condition is a radical mode of literary articulation. With it, the current models of criticism-world literature, the global novel, postcolonial and transatlantic studies-are undermined, while the very notions of margin and center are ultimately disolved. Oswaldo Zavala contends that Bolano deliberately dismantles the symbolic capital of the Western literary tradition by generating a counterhegemonic horizon of meaning that arises from and defines Latin American writing. The book offers innovative readings ofDistant Star,By Night in Chile,The Savage Detectives,Last Evenings on Earthand2666, among other works. It ultimately demonstrates that Bolano transcends the neoliberal dream of a global consciousness by revealing the discontinuous, contingent and savage reality of our pernicious modernity. Bolano forges the most urgent critique of 21st century Latin American and Western literature alike.